About Urban Mega Regions : Knowns And Unknowns - Yusuf, Shahid, 1949- 1949- (The World Bank, 2007)
Mega urban regions are not a passing phenomenon. They are likely to persist and to enlarge their economic footprints because they benefit from the advantages of market scale, agglomeration economies, location, and the increasing concentration of talented workers. Metropolitan regions which are polycentric, relatively well managed, and have invested heavily in transport infrastructure are able to contain some of the problems attendant upon a concentration of people and industry. Moreover, with energy and water resources becoming relatively scarce and many countries anxious to preserve arable land for farming, the economic advantages of densely populated urban areas are on the rise because they have a lower resource utilization quotient. During the next 15 years, mega urban economies could coalesce in three Southeast Asian locations: Bangkok, Jakarta, and the Singapore-Iskander Development Region (IDR, South Johor). The Bangkok and Jakarta (Jabotabek) metropolitan regions have passed the threshold at least in terms of population size but they have yet to approach the industrial diversity, dynamism, and growth rates of a Shanghai or a Shenzhen-Hong Kong region. Singapore, if coupled with IDR, has the potential but it is still far from being an integrated urban region. This paper examines the gains from closer economic integration and the issues to be settled before it could occur. The paper notes that a tightening of localized economic links between two sovereign nations through the formation of an urban region would involve a readiness to make long-term political commitments based on a widely perceived sense of substantial spillovers and equitably shared benefits. Delineating these benefits convincingly will be essential to winning political support and a precondition for a successful economic flowering